INVERTED INTERNAL LIMITING MEMBRANE FLAP TECHNIQUE FOR TREATMENT OF MACULAR HOLE RETINAL DETACHMENT IN HIGHLY MYOPIC EYES. Issue 12 (December 2018) - Takahashi, Hiroyuki; Inoue, Makoto; Koto, Takashi; Itoh, Yuji; Hirota, Kazunari; Hirakata, Akito
Abstract : Purpose: To compare the efficacy of vitrectomy with inverted internal limiting membrane (ILM) flap to complete removal of the ILM for the treatment of macular hole (MH) retinal detachment in highly myopic eyes. Methods: Pars plana vitrectomy with inverted ILM flap technique (16 eyes; inverted group) or with the complete removal of the ILM (16 eyes; removed group) was performed in patients with high myopia with MH retinal detachment. The rate of retinal reattachment and MH closure, the best-corrected visual acuities, and the integrity of the foveal microstructures in the optical coherence tomographic images were compared. Results: Thirteen eyes (81%) in the inverted group and 15 eyes (93%) in the removed group had retinal reattachment after the initial surgery ( P = 0.30). The MH was closed significantly more often in the inverted group (75%) than in the removed group (25%; P = 0.006). The postoperative best-corrected visual acuity was significantly better in the inverted group ( P = 0.04). The number of eyes with outer nuclear layer, external limiting membrane, and ellipsoid zone lines at the closed MH was not significantly different in the two groups. Conclusion: The inverted ILM flap technique with the presence of bridging tissue over the MH is effective in closing the MH and improving the postoperative best-corrected visual acuity in eyes with MH retinal detachment by bridging tissue over the MH. Abstract : The results showed that the inverted internal limiting membrane flap technique had higher macular hole closure rates and better visual outcome than the complete removal of the internal limiting membrane in eyes with a macular hole retinal detachment.